The complete chloroplast genome of Uncaria macrophylla Wall. (Rubiaceae) and its phylogenetic analysis. Issue 5 (4th May 2022) - Zhang, Ni; Song, Junrong; Liu, Hanfei; Li, Fei; Pan, Weidong
Abstract: Uncaria macrophylla Wall. 1824 is one of the five original plants of Uncariae Ramulus cum Uncis, and its molecular genetic relationship with other four remains unclear. Here, we reported the complete chloroplast genome of U. macrophylla . The chloroplast genome is 155, 145 bp in length, which includes paired inverted repeat regions of 25, 665 bp, a large single-copy region of 85, 758 bp and a small single-copy region of 18, 057 bp. In total, 127 genes were predicted, including 81 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. The phylogenetic analysis based on whole chloroplast genome sequences showed that U. macrophylla is closely related to U. rhynchophylla .